microRNAs in parasites and parasite infection - Zheng, Yadong (Landes Bioscience, 2013)
miRNAs, a subclass of small regulatory RNAs, are present from ancient unicellular protozoans to parasitic helminths and parasitic arthropods. The miRNA-silencing mechanism appears, however, to be absent in a number of protozoan parasites. Protozoan miRNAs and components of their silencing machinery possess features different from other eukaryotes, providing some clues on the evolution of the RNA-induced silencing machinery. miRNA functions possibly associate with neoblast biology, development, physiology, infection and immunity of parasites. Parasite infection can alter host miRNA expression that can favor both parasite clearance and infection. miRNA pathways are, thus, a potential target for the therapeutic control of parasitic diseases.